Treatment of tannery wastewater by a hybrid electrocoagulation/electrodialysis process - Deghles, Abdalhadi; Kurt, Ugur (ELSEVIER SCIENCE SA, 2016)
Globally, the leather industry is currently undergoing radical transformation due to pollution and discharge legislations. The present study is based on the investigation of performance of a hybrid electrocoagulation/electrodialysis process for the removal of COD, NH3-N, Cr and color in tannery wastewater. Effects of current density and electrolysis time were analyzed to optimize the electrocoagulation process with aluminum either iron electrodes. The optimized electrocoagulation process was then integrated with electrodialysis (ED) for the treatment of tannery effluents and was found that the hybrid process was capable of promoting the quality of the treated tannery wastewater. In case of treated tannery by EC with aluminum electrodes, ED process was effectiveness where the removal efficiency of COD, NH3-N, Cr and color were 92,100,100,100% respectively corresponds to conductivity value of 0.371 mS/cm at 45 minute. While, in the case of treated tannery by EC with iron electrodes, ED process was also efficient for removal pollutants, the removal efficiency of COD, NH3-N, Cr and color were 87,100,100,100% respectively corresponds to conductivity value of 1.5 mS/cm at 75 minute. It is noticeable that the effluent treated with combined EC-ED techniques presents very similar values for the same parameter as the ones presented by normal feed water. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Tannery effluents; Electrodialysis; Bipolar membrane; Zero effluents; Legislation; Electrocoagulation; ELECTROCHEMICAL OXIDATION; REMOVAL; DECOLORIZATION; COAGULATION; POLLUTANTS; PURIFICATION; SEPARATION; REDUCTION; EFFLUENTS; Energy & Fuels; Engineering